Hubungan Tingkat Stres dengan Perilaku Merokok pada Remaja Laki-Laki di SMA Saraswati 1 Denpasar - Putu Rias Andreani; Ni Kadek Muliawati; Ni Luh Gede Puspita Yanti (Jurnal Akademika Baiturrahim Jambi, 2020)
AbstractSmoking is a behavior that is very easily seen in everyday life. At this time cigarettes are not only consumed by adults, smoking is also one of the most common juvenile delinquents which is about 44,5% smoking consumed by teenagers. The cause of smoking among teenagers one of which is due to stress. This study aimed to to know the relationship of beetween the level stres with smoking behavior toward the teenagers. Method : This study used cross sectional method. The number of samples of this research was 65 people collecting by purposive sampling technique. The data collected by stress and smoking behavior questionnaire. Result : the teenagers have middle level of stress as much as 27 people (41,5%) and 39 teenagers (60%) confessed who smoke strong. Rank Spearman test results obtained p = 0,000 with a significance value of p<0.05, so 0.000 <0.05. That means there is significant relationship between stress level with smoking behavior teenagers. Discussion : stress levels will be followed by smoking behavior, at a young age it is expected that the PKPR program at the Public Health Center will be improved so that adolescents better understand the effects of the dangers of smoking.